2018
DOI: 10.2174/1568009617666170427103732
|View full text |Cite
|
Sign up to set email alerts
|

Targeting STEAP1 Protein in Human Cancer: Current Trends and Future Challenges

Abstract: Cancer is a global health issue that impairs the life quality of patients and origins thousands of deaths annually worldwide. Six-transmembrane epithelial antigen of the prostate (STEAP1) was identified to be overexpressed in several types of cancers, namely in prostate cancer (PCa). Considering its secondary structure, associated with its location in the cell membrane, has been suggested a role in intercellular communication between tumour cells. Taking into account its high specificity and overexpression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 0 publications
0
41
0
Order By: Relevance
“…Since its discovery in 1999 as a multispan membrane protein highly expressed on prostate cancer cells ( 1 ), six-transmembrane epithelial antigen of the prostate 1 (STEAP1) emerged as a cancer antigen expressed in various human cancers, including prostate, bladder, colorectal, lung, ovarian, and breast carcinoma and Ewing sarcoma. Because its expression in physiological tissues is minimal and mainly confined to the prostate gland ( 2 ), STEAP1 represents a potentially attractive therapeutic tool as both a cancer biomarker and a target for anticancer therapies ( 2 4 ). Indeed, several strategies for targeting STEAP1 in cancer have been explored; in 2007, a study reported the production and characterization of two monoclonal antibodies (mAb120.545 and mAb92.30) that bind STEAP1 with nanomolar affinity on prostate cancer cells and inhibit the growth of prostate and bladder tumor xenografts in mice ( 5 ).…”
mentioning
confidence: 99%
“…Since its discovery in 1999 as a multispan membrane protein highly expressed on prostate cancer cells ( 1 ), six-transmembrane epithelial antigen of the prostate 1 (STEAP1) emerged as a cancer antigen expressed in various human cancers, including prostate, bladder, colorectal, lung, ovarian, and breast carcinoma and Ewing sarcoma. Because its expression in physiological tissues is minimal and mainly confined to the prostate gland ( 2 ), STEAP1 represents a potentially attractive therapeutic tool as both a cancer biomarker and a target for anticancer therapies ( 2 4 ). Indeed, several strategies for targeting STEAP1 in cancer have been explored; in 2007, a study reported the production and characterization of two monoclonal antibodies (mAb120.545 and mAb92.30) that bind STEAP1 with nanomolar affinity on prostate cancer cells and inhibit the growth of prostate and bladder tumor xenografts in mice ( 5 ).…”
mentioning
confidence: 99%
“…Because of high expression in prostate and other cancers, STEAP1 has been identified as a promising candidate for therapeutic intervention using antibody-drug conjugates (ADCs), monoclonal antibodies, DNA vaccines, and small noncoding RNAs (13). Preclinical studies with 111 In or 89 Zr-MSTP2109A anti-STEAP1, an internalizing antibody, showed a correlation between the expression of STEAP1, radiolabeled antibody tumor uptake, and ADC efficacy.…”
mentioning
confidence: 99%
“…Furthermore, alpha-particle therapies targeting PSMA are often hindered by doselimiting toxicities (see below) (30). Approaches directed to STEAP1, a membrane protein highly upregulated in multiple cancer types, seemingly demonstrated AR-dependent STEAP1 expression in the prostate (31,32); however, studies investigating STEAP1 regulation have shown both ARdependent and independent regulation in various preclinical PCa models, suggesting a more nuanced role for AR in regulating STEAP1 expression (33,34). PSA has been primarily used as a PCa biomarker in the blood, yet serum levels of total PSA do not reliably discern PSA from malignant vs. healthy tissue nor provide reliable correlations with AR expression.…”
Section: Discussionmentioning
confidence: 99%